2016
DOI: 10.1016/j.archger.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, functional capacity, and oxidative stress changes in Brazilian community-living elderly subjects. A longitudinal study

Abstract: Fat reduction, muscle loss, central obesity increase, functional decline and worsening of plasma oxidative stress were observed during 2-year follow-up. Some of the risk factors that were identified could be modified to help prevent functional decline in elderly. The factors deserving attention include hypertension, arthritis/arthrosis and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 68 publications
3
13
1
2
Order By: Relevance
“…The literature has evidenced that functional capacity level can be improved or maintained by performing some physical exercises, or at least its decline rate can be minimized. Inclusion in a regular exercise program can be a kind of effective intervention to reduce or even prevent the number of functional declines associated with aging (11) ; however, this was not found in this study.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The literature has evidenced that functional capacity level can be improved or maintained by performing some physical exercises, or at least its decline rate can be minimized. Inclusion in a regular exercise program can be a kind of effective intervention to reduce or even prevent the number of functional declines associated with aging (11) ; however, this was not found in this study.…”
Section: Discussioncontrasting
confidence: 58%
“…This clinical profile may have negatively influenced the scores of issues relating to the physical domain of the WHOQOL-Bref in the present study. Furthermore, the literature points out that disability due to chronic morbidities of the musculoskeletal system can influence a decrease in score on the physical domain in evaluating the quality of life 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Elderly people living in the community and suffering from loss of muscle mass and central obesity have worse functional performance in basic and instrumental activities. Also, female and older individuals are independent risk factors associated with a decline in instrumental activities (13) .…”
Section: Discussionmentioning
confidence: 99%
“…No longitudinal studies that identified the occurrence of changes in functional capacity and physical performance of community-dwelling elderly concurrently were found, but only investigations on functional capacity 7,9,13 . According to Pinheiro et al 14 , information on the functional health of community-dwelling elderly based on direct measures (physical tests) is still scarce.…”
Section: Introductionmentioning
confidence: 99%